A promise to Nadia / Zana Muhsen with Andrew Crofts - Muhsen, Zana (Little, Brown, 2000)
Moving true-life story of a young woman's 10-year attempt to free her abducted sister fromYemeni slavery. Sequel to the int'l bestselling SOLD, which has sold over 100,000 paperbacks in Warner.